A white horse with wings - Davies, Anthea; Bryan, Brigitte (New York : Macmillan, 1968)
A retelling of five tales includes'A White Horse with Wings,''Tam Lin,''Alcestis,''Aucassin and Nicolette,' and'The Horn of Healing.'
Keywords: Tales